The Twelve Cranial Nerves of Christmas: Mnemonics, Rhyme, and Anatomy – Seeing the Lighter Side. Issue 6 (3rd January 2019) - Smith, Claire F.; Border, Scott
Abstract : Anatomy, has in history, been linked to helpful ways to remember structures, branches of nerves, structures passing through foramina, etc. Scalp is even a mnemonic in itself (S kin, C onnective tissue, A poneurosis, L oose areolar tissue, P ericranium). There has been concern by some educators that using mnemonics or rhymes promotes a surface approach to learning and is unhelpful in establishing long‐term and meaningful deep learning. This article argues that mnemonics and rhyme can be used, in the appropriate way, at the right time, by students as an important learning strategy. That strategy can help lay a foundation of knowledge to be developed and later built upon, or simply recall information more easily. Mnemonics, like all information that is to be recalled, is consolidated by rehearsal. In examining the neuroanatomy of learning theories, it is therefore possible to suggest that when students begin to learn an area of anatomy, such as the cranial nerves, using a mnemonic or rhyme, it can help students remember the names and facilitate the engagement of the working memory processes assisting the student to build a construct for subsequent deeper layers of knowledge. Modern approaches to anatomy education involve a myriad of learning opportunities, but educators must assess the value of each one before recommending them to students. It appears that using mnemonics and rhyme is as valid today as it has been for centuries.